Comparison of bacterial communities on limnic versus coastal marine particles reveals profound differences in colonization. (24th April 2014) - Bižić‐Ionescu, Mina; Zeder, Michael; Ionescu, Danny; Orlić, Sandi; Fuchs, Bernhard M.; Grossart, Hans‐Peter; Amann, Rudolf
Summary: Marine and limnic particles are hotspots of organic matter mineralization significantly affecting biogeochemical element cycling. Fluorescence in‐situ hybridization and pyrosequencing of 16S rRNA genes were combined to investigate bacterial diversity and community composition on limnic and coastal marine particles > 5 and > 10 μm respectively. Limnic particles were more abundant (average: 1 × 10 7  l −1 ), smaller in size (average areas: 471 versus 2050 μm 2 ) and more densely colonized (average densities: 7.3 versus 3.6 cells 100 μm −2 ) than marine ones. Limnic particle‐associated (PA) bacteria harboured A lphaproteobacteria and B etaproteobacteria, and unlike previously suggested sizeable populations of G ammaproteobacteria, A ctinobacteria and B acteroidetes . Marine particles were colonized by P lanctomycetes and B etaproteobacteria additionally to A lphaproteobacteria, B acteroidetes and G ammaproteobacteria . Large differences in individual particle colonization could be detected. High‐throughput sequencing revealed a significant overlap of PA and free‐living (FL) bacteria highlighting an underestimated connectivity between both fractions. PA bacteria were in 14/21 cases more diverse than FL bacteria, reflecting a high heterogeneity in the particle microenvironment. We propose that a ratio of Chao 1 indices of PA/FL < 1 indicates the presence of rather homogeneously colonized particles. The identification of different bacterial families enriched on either limnic or marine particles demonstrates that, despite the seemingly similar ecological niches, PA communities of both environments differ substantially.